Space Research in Baldone Observatory - Eglitis, I.; Eglite, M. (Science and Innovation, 2024)
The Baldone observatory deals with the U-, B-, V-, R-, I-photometry and low resolution spectroscopy of carbon stars, the monitoring of small bodies of Solar system, and with the digitizing and processing of 24 300 plates from the Schmidt wide field telescope archive. The astronomers from the observatory are working to popularize astronomy.